A Brief Study on Recycling of Waste Paper - Meena, Jagram (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2015)
Energy harvesting also known as power harvesting or energy scavenging is the process by which energy is derived from external sources solar power, thermal energy, wind energy, salinity gradients, and kinetic energy, captured, and stored for small, wireless autonomous devices, like those used in wearable electronics and wireless sensor. Energy harvesters provide very small low-energy electronics. While the input fuel to some large-scale generation costs money (oil, coal, etc.), the energy source for energy harvesters is present as ambient background and is free. For example, temperature gradients exist from the operation of a combustion engine and in urban areas, there is a large amount of electromagnetic energy in the environment because of radio and television broadcasting.